Assessment of Rose Bengal Photodynamic Therapy on Viability and Proliferation of Human Keratolimbal Epithelial and Stromal Cells In Vitro - Chai, Ning; Stachon, Tanja; Nastaranpour, Mahsa; Li, Zhen; Seitz, Berthold; Ulrich, Myriam; Langenbucher, Achim; Szentmáry, Nóra (Klinische Monatsblätter für Augenheilkunde, 2023)
Purpose To investigate the effect of Rose Bengal photodynamic therapy (RB-PDT) on viability and proliferation of human limbal epithelial stem cells (T-LSCs), human corneal epithelial cells (HCE-T), human limbal fibroblasts (LFCs), and human normal and keratoconus fibroblasts (HCFs and KC-HCFs) in vitro.Methods T-LSCs and HCE-T cell lines were used in this research. LFCs were isolated from healthy donor corneal limbi (n = 5), HCFs from healthy human donor corneas (n = 5), and KC-HCFs from penetrating keratoplasties of keratoconus patients (n = 5). After cell culture, RB-PDT was performed using 0.001% RB concentration and 565 nm wavelength illumination with 0.14 to 0.7 J/cm2 fluence. The XTT and the BrdU assays were used to assess cell viability and proliferation 24 h after RB-PDT.Results RB or illumination alone did not change cell viability or proliferation in any of the cell types (p ≥ 0.1). However, following RB-PDT, viability decreased significantly from 0.17 J/cm2 fluence in HCFs (p < 0.001) and KC-HCFs (p < 0.0001), and from 0.35 J/cm2 fluence in T-LSCs (p < 0.001), HCE-T (p < 0.05), and LFCs ((p < 0.0001). Cell proliferation decreased significantly from 0.14 J/cm2 fluence in T-LSCs (p < 0.0001), HCE-T (p < 0.05), and KC-HCFs (p < 0.001) and from 0.17 J/cm2 fluence in HCFs (p < 0.05). Regarding LFCs proliferation, no values could be determined by the BrdU assay.Conclusions Though RB-PDT seems to be a safe and effective treatment method in vivo, its dose-dependent phototoxicity on corneal epithelial and stromal cells has to be respected. The data and experimental parameters applied in this study may provide a reliable reference for future investigations.
Keywords: photodynamic therapy; Rose Bengal; human cornea fibroblasts; keratocytes